Conservation opportunities through improved management of recently established protected areas in Southeast Asia - Sreekar, Rachakonda (2024)
Protected areas (PAs) play a crucial role in biodiversity conservation and climate change mitigation. However, ineffective management can lead to biodiversity loss and carbon emissions from deforestation. To address this issue and explore viable solutions, we assessed the impact of PA establishment on avoided deforestation in 80 Southeast Asian PAs using the synthetic control approach. Our results show that 36 PAs successfully prevented 78,910 ha of deforestation. However, the remaining 44 PAs lost 72,497 ha of forest, impacting the habitat of 226 threatened bird and mammal species. Effective management of these reserves could have potentially avoided up to 2.07 MtCO2e yr-1 in carbon emissions. We estimate that at least $17 million USD per year in additional funding is required to better manage these 44 ineffective PAs and reduce future emissions. Furthermore, we demonstrate that carbon markets have the potential to generate these funds by reducing carbon emissions from deforestation within protected areas. Our findings emphasize that improving PA management is an essential nature-based solution for conserving biodiversity and mitigating climate change.